2021
DOI: 10.3390/ijerph18179310
|View full text |Cite
|
Sign up to set email alerts
|

Is the Antibacterial Activity of Multi-Walled Carbon Nanotubes (MWCNTs) Related to Antibiotic Resistance? An Assessment in Clinical Isolates

Abstract: Antimicrobial resistance has spread globally, compromising the treatment of common infections. This feature is particularly harmful for nosocomial pathogens that can survive on hospital surfaces. Research studies have been conducted to evaluate new materials that are able to counteract the microbial growth and the colonization of the hospital environment. In this context, nanotechnologies have showed encouraging applications. We investigated the antibacterial activity of multi-walled carbon nanotubes (MWCNTs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…All of these types and concentrations of MWCNTs have been shown to suppress bacterial strains, but functionalized MWCNTs had a stronger inhibitory impact than pristine ones. 36 In addition to this, it was shown that the introduction of a low concentration of MWCNT (0.1%) into a poly(dimethylsiloxane) matrix could limit the adherence of E. coli by 20%. 36 There was a 60% decrease in the amount of E. coli that adhered to the poly(dimethylsiloxane) matrix as the concentration of MWCNT was raised to 1%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these types and concentrations of MWCNTs have been shown to suppress bacterial strains, but functionalized MWCNTs had a stronger inhibitory impact than pristine ones. 36 In addition to this, it was shown that the introduction of a low concentration of MWCNT (0.1%) into a poly(dimethylsiloxane) matrix could limit the adherence of E. coli by 20%. 36 There was a 60% decrease in the amount of E. coli that adhered to the poly(dimethylsiloxane) matrix as the concentration of MWCNT was raised to 1%.…”
Section: Introductionmentioning
confidence: 99%
“…36 In addition to this, it was shown that the introduction of a low concentration of MWCNT (0.1%) into a poly(dimethylsiloxane) matrix could limit the adherence of E. coli by 20%. 36 There was a 60% decrease in the amount of E. coli that adhered to the poly(dimethylsiloxane) matrix as the concentration of MWCNT was raised to 1%. 37 In another study, it was shown that Staphylococcus sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous reports in the literature reporting the successful applications of CNTs in biomedical fields such as in multidrug-resistant bacterial infections [25], drug delivery systems [12] anticancer materials [26], and biosensor [27]. In this article, an overview of different applications of CNTs such as antibacterial agents and bone-grafting/scaffolding in dentistry is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…New materials that can withstand the microbiological growth of some pathogens in the hospital environment have recently been tested. Using both native and functionalized versions of MWCNTs at concentrations of 50 and 100 g/ ml, different dosages of MWCNTs on the inhibitory effect were determined [20]. MWCNTs have additional advantages and potential features for use as inorganic llers in polymeric substrate reinforcement [21].…”
Section: Introductionmentioning
confidence: 99%